Pengaruh Rasio Tunggakan Dan Rasio Penagihan Terhadap Profitabilitas (Survey Pada PT. Bank National Nobu Tbk Cabang Palembang Square Periode 2018-2020) - Rina Atrijaya Suci; Harsi Romli; Lukita Tripermata (Training & Research Institute - Jeramba Ilmu Sukses, 2022)
This study aims to analyze the effect of the arrears ratio and collection ratio on profitability at PT Bank National Nobu Tbk Palembang Square Branch. The sample selection was determined by purposive sampling from the year of 2018 to 2020. The analytical model used in this study was a multiple linear regression analysis model. Based on the results of research and analysis conducted, it can be concluded that partially the ratio of arrears has no effect on profitability at PT Bank National Nobu Tbk Palembang Square Branch. While the billing ratio has an effect on profitability at PT Bank National Nobu Tbk. Meanwhile, the ratio of arrears and the ratio of collections together affects the profitability of PT Bank National Nobu Tbk. This research is expected to be additional literature on the topic of corporate profitability.